Postponement of the Inauguration of the Council Secretary at Bone Regency DPRD: Impact on Government Administration - Yusmar, Syarifuddin; Kahar, Abdul; HM, Syarifuddin; Asdar, Muhammad; ⁠Erviandy, ⁠Erviandy (Journal of Management and Administration Provision, 2024)
The delay in opening the DPRD Secretary in Bone Regency also underscores the issue of bureaucratic processes and how it affects governance more generally. This paper evaluates administrative, political and social consequences of the delay through a qualitative literature review approach that relies on accredited national and international journals and applicable regulatory documents. The results indicate that the unfilled office of the Secretary interfered with the administrative coordination between the executive and the legislative branch and caused delays in making decisions, budget planning, and even formulating legislative policies. Politically, this demotion of the Speaker of the DPRD to provide a recommendation without a valid reason served only to create more tension between the two branches, undermine cooperation, and extend the periods of political confrontations. In social terms, the halted process gave the impression of lack of transparency and political interference, as it weakened the institutional trust of the population in government and destroyed the reputation of democratic governance. The analysis of regulatory institutions also demonstrates that Government Regulation No. 18 of 2016 allows the Speaker a high degree of discretionary power, which, when abused, may hinder the running of the administrative machinery and undermine institutional credibility. To overcome these, the research suggests reforms to demystify the processes, improve communication between the executive and legislative departments, redefine the power of the Speaker to be objective and improve transparency with oversight and mediation procedures. It is also necessary not only to avoid administrative stalemates but also to ensure that people have faith in democratic procedures. The example of Bone Regency can therefore underpin valuable lessons regarding the connection between procedural compliance, institutional stability and the quality of governance during the era of decentralization in Indonesia.